2006
DOI: 10.1073/pnas.0507947103
|View full text |Cite|
|
Sign up to set email alerts
|

Human centromeric chromatin is a dynamic chromosomal domain that can spread over noncentromeric DNA

Abstract: Human centromeres are specialized chromatin domains containing the centromeric histone H3 variant CENP-A. CENP-A nucleosomes are interspersed with nucleosomes containing histone H3 dimethylated at lysine 4, distinguishing centromeric chromatin (CEN chromatin) from flanking heterochromatin that is defined by H3 lysine 9 methylation. To understand the relationship between chromatin organization and the genomic structure of human centromeres, we compared molecular profiles of three endogenous human centromeres, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
142
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(154 citation statements)
references
References 41 publications
10
142
1
1
Order By: Relevance
“…Although additional studies are needed to determine whether genes inserted into the alphoid tetO -HAC may eventually be subject to silencing, our results and those obtained with other HACs (21,41) support the view that proximity to a functional kinetochore does not negatively affect gene expression. It is possible that, in the human genome, centromeric chromatin may be a privileged region for Pol II-transcribed genes, as previously shown for rice centromeres (43) and suggested by the resemblance of the centromeric chromatin profile to the downstream region of transcribed genes in human cells (39,44). Indirectly, this hypothesis is supported by our data on spreading of CENP-A chromatin to the 3′ end of NBS1 and transcriptional activity of genes in neocentromeres (reviewed in ref.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Although additional studies are needed to determine whether genes inserted into the alphoid tetO -HAC may eventually be subject to silencing, our results and those obtained with other HACs (21,41) support the view that proximity to a functional kinetochore does not negatively affect gene expression. It is possible that, in the human genome, centromeric chromatin may be a privileged region for Pol II-transcribed genes, as previously shown for rice centromeres (43) and suggested by the resemblance of the centromeric chromatin profile to the downstream region of transcribed genes in human cells (39,44). Indirectly, this hypothesis is supported by our data on spreading of CENP-A chromatin to the 3′ end of NBS1 and transcriptional activity of genes in neocentromeres (reviewed in ref.…”
Section: Discussionsupporting
confidence: 77%
“…This indicates that the CENP-A chromatin domain extends to beyond the gene insertion site. CENP-A enrichment at the 3′ NBS1 sequence may be explained by the ability of CENP-A chromatin to spread onto noncentromeric DNA (16,39,40). The observed stable gene expression in the HAC suggests that close proximity of the CENP-A domain does not prevent expression of Pol II-transcribed genes.…”
Section: Conversion Of Nbs1-and Vhl-yacs Into Bacs With a Loxp Cassetmentioning
confidence: 82%
See 1 more Smart Citation
“…Changes in inner kinetochore protein abundance in human cancer cell lines have demonstrated that centromeric domains expand relative to the underlying satellite array (Sullivan et al 2011). Human artificial chromosome assays provide further support for establishment and dosagedependent spreading of kinetochore-binding proteins to adjacent DNA (Lam et al 2006). With increased dosage, it is likely that other optimal regions of the genome might acquire ectopic localization of inner kinetochore proteins, perhaps coupling epigenetic Sequence optimality and centromere identity.…”
Section: Centromere Model Of Sequence Optimalitymentioning
confidence: 99%
“…Besides CENP-A, active centromeres display a specific profile of post-translational modifications on their associated histone H3-containing nucleosomes (Bergmann et al, 2011;Lam et al, 2006;Ribeiro et al, 2010;Sullivan and Karpen, 2004). This special chromatin, which has been termedx 'centrochromatin' (Sullivan and Karpen, 2004), suggests a functional link between the local chromatin environment and kinetochore function.…”
Section: Introductionmentioning
confidence: 99%